Nucleotide sequences of STE2 and STE3, cell type-specific sterile genes from Saccharomyces cerevisiae - Nakayama, N. (1985)
The nucleotide sequences of STE2 and STE3, cell type-specific sterile genes of Saccharomyces cerevisiae, were determined; major open reading frames encode 431 and 470 amino acids, respectively. STE2 and STE3 proteins seem to be folded in a similar fashion and are likely to be membrane-bound. Both consist of seven hydrophobic segments in each NH(2)-terminal region with a long hydrophilic domain in each COOH-terminal region. However, the two putative gene products do not exhibit extensive sequence homology. The STE2 protein has no obvious hydrophobic signal peptide; the NH(2) terminus of the STE3 protein might serve as a signal peptide. The STE2 transcript, 1.7 kb, was detected in MATa strains but not in MATα strains, while the STE3 transcript, also 1.7 kb, was detected only in MATα cells. In STE2, two canonical TATA sequences are located 18 and 27 bp upstream of the mRNA start site, which has been mapped 32 bp before the initiator ATG codon, while STE3 contains a similar sequence (TATAGA), which is preceded by a long AT sequence, 140 bp upstream of the initiator ATG codon. Transcription of STE2 in a cells seems to be enhanced by exogenous α-factor.